MYTHOLOGICAL NARRATIVE IN VIDEO GAMES AS A FORM OF MEDIA PROMOTION OF CULTURE (Heritage, 2023)
With the advent of digital media, a new game platform has been created that moves from the real environment to the virtual space. The application of modern technology and the Internet led to the creation of platforms dedicated to video games and the appearance of virtual players. Considering that we cannot see the game only as entertainment, but also as a medium that leads to social gathering, the game is also recognized as a tool for the promotion of various social values. The narrative of the video game directs the players to simultaneously educate themselves through the game, improve themselves and, through interaction with other players, change their identity and adopt different cultural values. Narratives based on the mythology of a nation become a medium for “storytelling” and the promotion of national culture.
Keywords: medium, video game, virtual space, narrative, culture